2017
DOI: 10.4236/aces.2017.73022
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Ionic Liquid 1-Ethyl-3-Methyl-Imidazolium Acetate ([EMIM][Ac]) in Enhanced Medium Oil Recovery

Abstract: Chemical flooding is one of the most efficient methods for Enhanced Oil Recovery (EOR). This study demonstrates the efficiency of mixing different concentrations of Ionic Liquid (IL), 1-Ethyl-3-Methyl-Imidazolium Acetate ([EMIM][Ac]), with Weyburn brine to improve a medium oil recovery, Weyburn oil, from an unconsolidated sand pack sample at room conditions. Effects of Slug Size (SS), IL + brine slug initiation time, and combining IL with alkali on the Recovery Factor (RF) were investigated. This study showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…For one of the scenarios the core samples were initially flooded with 1 pore volume of chemicals mixture then flushed by two pore volumes of brine. The optimum flow rate (2 cm 3 /min) was applied as injection rate for flooding experiments that were done to investigate the effect of chemical concentration, the chemical solution slug size, the initiation time for injecting the chemical mixture as well as the flow rate that was obtained from previous study [16]. The produced oil and water samples from the sand pack were collected in graduated tubes and then placed in a separator to determine the exact amount of recovered oil.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For one of the scenarios the core samples were initially flooded with 1 pore volume of chemicals mixture then flushed by two pore volumes of brine. The optimum flow rate (2 cm 3 /min) was applied as injection rate for flooding experiments that were done to investigate the effect of chemical concentration, the chemical solution slug size, the initiation time for injecting the chemical mixture as well as the flow rate that was obtained from previous study [16]. The produced oil and water samples from the sand pack were collected in graduated tubes and then placed in a separator to determine the exact amount of recovered oil.…”
Section: Methodsmentioning
confidence: 99%
“…2017) have found that the increase in the RF was not economical when the IL [EMIM][Ac] concentration rose beyond the optimum concentration[16].…”
mentioning
confidence: 99%
“…The relevant core sample physical property data were obtained from the laboratory experiments [14] and supplemented with CMG templates if needed. A summary of the rock and fluid properties is shown in Table 1.…”
Section: Reservoir Propertiesmentioning
confidence: 99%
“…The reservoir model used is a water-wet sandstone medium. The two-phase relative permeability for the base case utilized in this study is based on the laboratory flooding experiments [14]. The two-phase water oil relative permeability as a function of water saturation is shown in Table 2.…”
Section: Relative Permeabilitymentioning
confidence: 99%
“…In addition to the high performance at high-salinity and high-temperature conditions, ILs exhibit some behaviors making them more effective than surfactants. , From these unique properties, we can refer to their environmentally friendly, cost-effectivity, nontoxicity, nonflammability, high viscosity, high thermal and salinity stability, and changeability of their surface properties . The main advantages of ILs stemming from their outstanding properties which make them more attractive in the oil industry are the ability to prevent asphaltene precipitation, reduce oil viscosity, and break water-in-oil emulsions. , Recently, they have been used as a surface-active chemical to reduce the interfacial tension (IFT) between aqueous and nonaqueous phases and to change the wettability of the rock surface toward more water-wet conditions. , The selection of the appropriate type of IL is an important step that should be performed cautiously since some of them are unsuitable for EOR purposes mainly because of an inactive surface. , …”
Section: Introductionmentioning
confidence: 99%